In-vivo Imaging of Mitochondrial Depolarization of Myocardium With Positron Emission Tomography and a Proton Gradient Uncoupler - Alpert, Nathaniel M.; Pelletier-Galarneau, Matthieu; Kim, Sally Ji Who; Petibon, Yoann; Sun, Tao; Ramos-Torres, Karla M.; Normandin, Marc D.; El Fakhri, Georges (Frontiers in Physiology, 2020)
Background: We recently reported a method using positron emission tomography (PET) and the tracer 18F-labeled tetraphenylphosphonium (18F-TPP+) for mapping the tissue (i.e., cellular plus mitochondrial) membrane potential (ΔΨT) in the myocardium. The purpose of this work is to provide additional experimental evidence that our methods can be used to observe transient changes in the volume of distribution for 18F-TPP+ and mitochondrial membrane potential (ΔΨm). Methods: We tested these hypotheses by measuring decreases of 18F-TPP+ concentration elicited when a proton gradient uncoupler, BAM15, is administered by intracoronary infusion during PET scanning. BAM15 is the first proton gradient uncoupler shown to affect the mitochondrial membrane without affecting the cellular membrane potential. Preliminary dose response experiments were conducted in two pigs to determine the concentration of BAM15 infusate necessary to perturb the 18F-TPP+ concentration. More definitive experiments were performed in two additional pigs, in which we administered an intravenous bolus plus infusion of 18F-TPP+ to reach secular equilibrium followed by an intracoronary infusion of BAM15. Results: Intracoronary BAM15 infusion led to a clear decrease in 18F-TPP+ concentration, falling to a lower level, and then recovering. A second BAM15 infusion reduced the 18F-TPP+ level in a similar fashion. We observed a maximum depolarization of 10 mV as a result of the BAM15 infusion. Summary: This work provides evidence that the total membrane potential measured with 18F-TPP+ PET is sensitive to temporal changes in mitochondrial membrane potential.